2004
DOI: 10.1007/s11101-004-2883-5
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic paths towards scalaranes: Assembling the scalaranic skeleton and further transformations

Abstract: The family of scalaranic sesterterpenoids has been known since the early 70s, but they have attracted the attention of synthetic organic chemists only in the last decade. These marine natural products are considered secondary metabolites of marine organisms and have shown promising biological properties. Synthetic approaches towards scalaranes are discussed in the present review. Scalaranes are quite complex compounds, with many chiral centers and their transformations are strongly directed by steric effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Table S2: (a) Bond distances (Å) and (b) angles ( • ) for compound 8 (CCDC 2116545). 1 H, 13 C and 2D NMR spectra of compounds (6)(7)(8)(9)(10)(11).…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table S2: (a) Bond distances (Å) and (b) angles ( • ) for compound 8 (CCDC 2116545). 1 H, 13 C and 2D NMR spectra of compounds (6)(7)(8)(9)(10)(11).…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…[3,8]. However, a broader investigation of scalaranes in medicinal chemistry studies is still hampered by their relative scarcity in natural sources and a lot of efforts have been put on the elaboration of pathways for their target synthesis [10]. The structural complexity of the scalarane architecture is connected to their polycyclic backbone, stereochemical issues and specific oxygenations.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of scalaranes has already been summarized, together with a description of isolation and biological activities, in a review from 2004. 126 Since then, it has remained an active area of research, evidenced by successful syntheses of the scalaranes (+) scalarolide (218), 9,127 ( ) sester statin 4 (217), 128,129 its epimer ( ) sesterstatin 5 (220) 128,129 and (+) 16 deacetoxy 12 epi scalarafuranacetate (221) 130,131 recently appearing in the literature. Notably, the latter three completed targets exhibit potent cytotoxic activity, likely stimulating further synthetic and biological studies on related natural products and structural analogs within this compound class.…”
Section: Miscellaneous Tetracarbocyclic Sesterterpenoidsmentioning
confidence: 99%
“…The study also confirmed the potential of scalarane compounds as dual inhibitors of topoisomerase II and Hsp90, which are considered as important molecular targets in the development of anticancer drugs. Owing to the biological significance of these molecules, considerable effort has been made to discover or synthesize them [11,21,22,23].…”
Section: Introductionmentioning
confidence: 99%